2016
DOI: 10.1039/c6nr00400h
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen reduction catalyzed by gold nanoclusters supported on carbon nanosheets

Abstract: Nanocomposites based on p-mercaptobenzoic acid-functionalized gold nanoclusters, Au102(p-MBA)44, and porous carbon nanosheets have been fabricated and employed as highly efficient electrocatalysts for oxygen reduction reaction (ORR). Au102(p-MBA)44 clusters were synthesized via a wet chemical approach, and loaded onto carbon nanosheets. Pyrolysis at elevated temperatures led to effective removal of the thiolate ligands and the formation of uniform nanoparticles supported on the carbon scaffolds. The nanocompos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 42 publications
3
39
0
Order By: Relevance
“…We integrated polyvinyl pyrrolidone (PVP)-protected Au nanoclusters with reduced graphene oxide (RGO) as the catalyst [61] and found that the nanocomposite possessed markedly higher long-term stability in ORR than Pt/C. Subsequently, we fabricated nanocomposite based on p-mercaptobenzoic acid-functionalized Au nanoclusters, Au 102 (p-MBA) 44 , and porous carbon nanosheets [62]. The best sample in the series composite exhibited slightly positive onset potential, but much higher long-term durability than Pt/C.…”
Section: Au Clusters For Orrmentioning
confidence: 99%
“…We integrated polyvinyl pyrrolidone (PVP)-protected Au nanoclusters with reduced graphene oxide (RGO) as the catalyst [61] and found that the nanocomposite possessed markedly higher long-term stability in ORR than Pt/C. Subsequently, we fabricated nanocomposite based on p-mercaptobenzoic acid-functionalized Au nanoclusters, Au 102 (p-MBA) 44 , and porous carbon nanosheets [62]. The best sample in the series composite exhibited slightly positive onset potential, but much higher long-term durability than Pt/C.…”
Section: Au Clusters For Orrmentioning
confidence: 99%
“…First of all, chronoamperometric measurements were performed at + 0.6 V in an O 2 -saturated 0.1 M KOH solution. [14] Additionally, the porous structure might facilitate the transport of electrolytes as well as reaction intermediates, which was favorable for the reaction kinetics. However, there was about 16 % loss for the commercial Pd black under the same conditions, indicating more robust stability of Pd/CNS-20 % for ORR.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4] In the past decades, noble metal clusters have been gaining extensive attention, thanks to their versatile applications in sensing and labeling, [5] optoelectronics, [6] and catalysis. [13][14][15] ORR is a key reaction which largely determines the efficiency of metal-air batteries and fuel cells, and Pt-based nanomaterials have been recognized as the most effective electrocatalysts for ORR. [13][14][15] ORR is a key reaction which largely determines the efficiency of metal-air batteries and fuel cells, and Pt-based nanomaterials have been recognized as the most effective electrocatalysts for ORR.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nørskov et al reported a volcano plot which indicates the trends in ORR activity as a function of the oxygen binding energy [4]. Au nanoclusters and nanoparticles with porous carbon supports for ORR also studied in some papers [8,9]. On the other hand, gold (Au) was reported as a less active metal for ORR, exhibiting twoelectron reduction pathway, because of the too weak binding of oxygen on Au surface [3,5].…”
Section: Introductionmentioning
confidence: 99%